Missed chronic disease prevention opportunities in primary health care clinics in Turkey - (:unkn) unknown (My University, 2009)
• Objective: The study aimed to investigate the state of practices for the prevention of chronic diseases in outpatient clinics. • Material and Method: Study design was primary health care center clients based cross sectional. Study which was held in a urban Family Medicine Center in a northwest Anatolia city Eskisehir (Turkey). The study population consisted of 585 people which were selected randomly according to their application order. Participants were asked; if they were questioned by their physician about major risk factors (smoking, obesity, diabetes mellitus, hypertension, coroner heart disease in family, glysemic level, cholesterol level) and regular exercise practice according to Primary Care 2006 Guidelines. If not it was termed as 'missed opportunities' for chronic disease screening and prevention and management. • Results: There were around the 90.0 %missing opportunities screening and management of obesity in outpatient clinics. Missing opportunities were approximately 80.0% for prevention and cessation management of smoking. There were very high missing opportunities for hypertensive patients' monitoring and risk factor management. • Conclusion: Missed opportunities are a common problem in prevention from chronic disease. Especially preventive actions, health education and asking about risk factors are neglected in outpatient clinics and primary health care services.
Keywords: Chronic disease; Missed opportunities; Prevention; Primary health care; Screening